2017
DOI: 10.18273/revmed.v30n1-2017002
|View full text |Cite
|
Sign up to set email alerts
|

Conocimientos, actitudes y prácticas asociados a diarrea aguda en la zona norte de Bucaramanga. Estudio observacional analítico, 2014 - 2015

Abstract: RESUMENIntroducción: la diarrea aguda y la mortalidad por diarrea continúan siendo un problema de salud pública a nivel mundial, especialmente en los países de ingreso medio o bajo. Gran parte de las enfermedades diarreicas son prevenibles mediante el acceso al agua potable y a servicios adecuados de saneamiento e higiene. Objetivo: caracterizar los conocimientos, actitudes y prácticas de cuidadores de niños menores de cinco años asociados a prevalencia de diarrea. Materiales y métodos: estudio observacional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…This underscores the importance of hand washing as a key preventive measure to control and prevent diarrhea in children. 11,12 Lopez et al 13 conducted a study with 3,432 infants, analyzing the incidence of acute watery diarrhea and the effect of different probiotics (Lactobacillus spp, Bifidobacterium spp, Streptococcus spp, or S. boulardii) administered alone or in combination at various doses of the sixteen clinical trials reviewed, seven focused specifically on L. rhamnosus or S. boulardii. The results revealed that the incidence of acute watery diarrhea was reduced to 9% in the group that received probiotics, compared to 18% in the control group, which is equivalent to a risk reduction (RR) of 0.52; with a 95% confidence interval of 0.38 to 0.72.…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the importance of hand washing as a key preventive measure to control and prevent diarrhea in children. 11,12 Lopez et al 13 conducted a study with 3,432 infants, analyzing the incidence of acute watery diarrhea and the effect of different probiotics (Lactobacillus spp, Bifidobacterium spp, Streptococcus spp, or S. boulardii) administered alone or in combination at various doses of the sixteen clinical trials reviewed, seven focused specifically on L. rhamnosus or S. boulardii. The results revealed that the incidence of acute watery diarrhea was reduced to 9% in the group that received probiotics, compared to 18% in the control group, which is equivalent to a risk reduction (RR) of 0.52; with a 95% confidence interval of 0.38 to 0.72.…”
Section: Introductionmentioning
confidence: 99%
“…Según la dimensión lavado de manos encontramos en el resultado de esta investigación (Grafico 2) donde el 58% no aplican prácticas preventivas y el 42 % si aplican prácticas preventivas para evitar las enfermedades diarreicas agudas donde se observa que la mayor proporción de madres usaban agua corriente para la adecuada higiene de manos en un 88%, respecto al uso de toalla con la que se secan las manos no es personal por lo que no aplica prácticas preventivas un 86%,resultados semejantes al de Tejada C. 11 donde las madres no se lavan las manos antes y después de manipular alimentos, después de ir al baño, manipular desechos un 47.5% resultados preocupantes ya que es un comportamiento primordial parte de una estrategia para poder evitar infecciones a futuro. Al contrario en estudios realizados por Carrillo K. 8 donde el 66.67% y Abreu P. 7 et al el 45.3% sí aplican adecuadamente la práctica de higiene de manos.…”
Section: Ivb Discusiónunclassified